Dynamic Friction-Based Force Feedback for Tendon-Sheath Mechanism in NOTES System - Do, Thanh Nho (2015)
Tendon-sheath mechanism (TSM) is commonly used in flexible endoscopic systems because of its high flexibility, light weight, and easy transmission. Due to the size constraints and sterilization problems, traditional sensors cannot be placed at the tool tips of robotic arms. In addition, nonlinear friction and backlash hysteresis cause many challenges to predict the desired force when the system inside the human’s body. It is extremely difficult to provide the force information to haptic devices and subsequently to the users. In this paper, a new scheme of dynamic friction model for a pair of TSMs is proposed to estimate the force at distal end of endoscopic system. In comparison with current approaches in the literature, our model is able to provide continuous force information. The model is able to predict distal force with any sheath shapes. An experimental setup is designed to measure the friction force in the TSM. Finally, the validity of the proposed model approach is confirmed with a good agreement between the estimated values and real experimental data.